2004
DOI: 10.1002/elan.200302896
|View full text |Cite
|
Sign up to set email alerts
|

Determination of an Ethylene Bisdithiocarbamate Based Pesticide (Nabam) by Cobalt Phthalocyanine Modified Carbon Ink Electrode

Abstract: A phthalocyanine based sensor, for anodic detection of sodium ethylene bisdithiocarbamate (Nabam) by coating a mixture of cobalt phthalocyanine (CoPC) modified carbon ink on the surface of a glassy carbon electrode, has been described. The modified ink was prepared by mixing three percent of cobalt phthalocyanine into carbon ink and then diluting the mixture with cyclohexanone in w/w ratio of 1/9. A suitable portion (or 1 mL) of ink mixture was then dipcoated on a rotating disk glassy carbon electrode. The mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Some of these forms of modification attempt to enhance the adsorption of dithiocarbamates to enhance detection sensitivity e.g., PTFE [ 41 , 42 ] and mercury amalgams [ 49 ]. Others apply catalysts to facilitate electron-transfer between DTFs and the electrode: the most commonly-identified are metallophthalocyanines [ 45 , 46 ] and metal nanoparticles [ 55 , 57 ] to catalyze anodic detection of DTFs. While all of the catalysts reportedly impart enhanced sensitivity, none of them increase specificity: the broad electrocatalytic effects of metallophthalocyanines [ 61 ] and metal nanoparticles [ 62 ] are widely-known.…”
Section: Advances In Dtfs Detectionmentioning
confidence: 99%
“…Some of these forms of modification attempt to enhance the adsorption of dithiocarbamates to enhance detection sensitivity e.g., PTFE [ 41 , 42 ] and mercury amalgams [ 49 ]. Others apply catalysts to facilitate electron-transfer between DTFs and the electrode: the most commonly-identified are metallophthalocyanines [ 45 , 46 ] and metal nanoparticles [ 55 , 57 ] to catalyze anodic detection of DTFs. While all of the catalysts reportedly impart enhanced sensitivity, none of them increase specificity: the broad electrocatalytic effects of metallophthalocyanines [ 61 ] and metal nanoparticles [ 62 ] are widely-known.…”
Section: Advances In Dtfs Detectionmentioning
confidence: 99%
“…Phthalocyanine complexes of transition metals, especially cobalt phthalocyanine (CoPc), are large macrocyclic molecules with applications in the fields of conductive polymers, chemical sensors, electrochromism, etc ., due to their low cost facileness of large-scale preparation, and chemical and thermal stability. Numerous research groups have considered CoPc modified electrodes for determining sulfur containing compounds such as carbaryl [ 22 ], ethylene bisdithiocarbamate-based pesticides [ 23 ], cystine [ 24 ], and zinc pyrithione [ 25 ]. However, CoPc modified electrodes were rarely utilized for cosmetic product analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Ethylenethiourea (imidazolidine-2-thione, ETU), an intermediate in ethylene bisdithiocarbamates (EBDCs) formulations can be generated from EBDCs by aeration or during cooking processes and is present in most EBDCs-treated crops. 10,11 EBDCs are an agriculturally important group of fungicides. In 1987, the US Environmental Protection Agency (EPA) monitored the ETU residual amount in 5888 food items and showed that 18% of the samples contain residue of ETU.…”
Section: Introductionmentioning
confidence: 99%